Pelayanan kefarmasian dan edukasi pada peserta khitanan massal di Desa Tanjung Kidul - Fahmi Dimas Abdul Azis; Rokayah; Endah S; Royhan Hanin S; Rio Renaldi H (Jurnal Dedikasi Masyarakat, 2022)
The Mass Circumcision event took place on June 13, 2022, at Tanjung Kidul Village, Paiton District, Probolinggo Regency, located in the East Java Province. The community in the village of Tanjung Kidul actively participates as partners in the circumcision activities. Circumcision, referred to as "circumcision" or "male genital cutting," is a surgical intervention involving the partial or complete removal of the prepuce. This practice is commonly undertaken for grounds pertaining to societal, religious, sanitary, or aesthetic considerations. Furthermore, circumcision has been found to potentially mitigate difficulties linked to specific medical diseases, including phimosis and paraphimosis. In the context of Indonesia, there exists a significant prevalence of independent drug use among the populace. The primary purpose of this intervention is to alleviate ailments, enhance physical stamina, and facilitate the performance of routine tasks. The chemist played a vital role in the provision of pharmaceutical services during the mass circumcision activity, primarily by dispensing medication and offering educational guidance on its proper administration post-circumcision. This endeavor entails a cooperative effort among several occupations, namely nurses and chemists. The primary responsibility of the chemist in this endeavor is to optimize the efficacy of medication administration for those undergoing circumcision. Community service programs were initiated by pharmacists from the Indonesian Association of Pharmacists Branch Management (IAI PC Kab. Probolinggo), academics from Hafshawaty Zainul Hasan STIKes lecturers and students, and nurses from the Indonesian National Nurses Association (PPNI). Indicators utilized for the evaluation of activities encompass the seamless execution of the event, the level of participant attendance, the appropriateness of primary responsibilities and functions, and the collection of activity testimonies. The execution of activities has been conducted in a systematic and organized fashion, facilitated by effective coordination between the committee, village officials, and participants. The successful implementation of the activity is evidenced by the results of a questionnaire, which revealed that 28 participants were highly satisfied, and 4 participants expressed satisfaction.